Treatment tactics and strategy for complicated colon cancer in the settings of surgical department - B.O. Matviychuk; R.L. Bokhonko; A.V. Gotsulenko; O.B. Matviychuk; A.D. Kvit; A.M. Lavryk; Ya.Z. Pater; O.М. Pylypiak; S.D. Boyarchuk (Медицина неотложных состояний)
Background. Colon cancer is often primarily detected due to complications such as acute obstruction, perforation and peritonitis, acute bleeding. With few exceptions, emergency care for patients with complicated colon cancer is provided in surgical departments of hospitals at all levels. Urgent surgery solves mainly the tactical task, elimination a life-threatening complication of colon cancer, while strategical one, the radical intervention, is being frequently postponed due to subjective and objective reasons. As a result, 5-year survival rate of patients operated for complications of colon cancer is 3–38 %. Aim: to determine a rational combination of tactical and strategic aspects of treatment in patients with complicated colon cancer. Materials and methods. Retrospective study analyzed treatment outcomes of 102 patients with complicated colon cancer who were urgently hospitalized to the Center of surgery and oncology No. 2 of the Saint Panteleimon Hospital of the First Lviv Territorial Medical Union (Lviv) in 2021–2024. Complications of colon cancer included: acute obstruction — 75 (73.5 %), peritonitis caused by tumor perforation — 16 (15.7 %), bleeding — 11 (10.8 %). X-ray examination of the abdomen revealed free gas under the diaphragm in 16 (15.7 %) patients, and the presence of Kloiber cups in 75 (73.5 %). Computed tomography with intravenous contrast was used before surgery in 86 (64.3 %) cases: colon cancer was diagnosed in 82.3 %, metastatic liver damage — in 41.1 %, regional lymphadenopathy — in 21.3 %, peritoneal carcinomatosis, ascites — in 7.4 %. Results. Preoperative preparation aimed mainly at the correction of homeostasis led to the elimination of acute intestinal obstruction in 9 (12.0 %) people. Usage of self-expanding nitinol stent had restored intestinal passage in 4 (5.3 %) patients with obstructive cancer of the sigmoid colon. Within 24 hours of hospitalization, 78 patients (76.5 %) underwent urgent surgery, including 62 (79.5 %) with acute obstructive ileus and 16 (20.5 %) with diffuse purulent-fecal peritonitis due to tumor perforation. Elimination of acute colon obstruction by conservative measures and stenting made it possible to perform delayed surgical interventions in 24 (23.5 %) patients after appropriate correction of homeostasis, anemia and concomitant pathology. Laparotomy revealed the following locations of colon cancer: cecum — 2 (2.2 %), hepatic flexure — 9 (10.0 %), transverse colon — 9 (10.0 %), splenic flexure — 21 (23.3 %), descending colon — 10 (11.1 %), sigmoid — 30 (33.4 %), rectosigmoid — 9 (10.0 %). Operations performed were: double-barreled ileostomy — 1 (1.1 %), cecostomy — 2 (2.2 %), colostomy — 31 (34.4 %), ileotransversostomy — 2 (2.2 %), right hemicolectomy — 19 (21.2 %), left hemicolectomy — 25 (27.8 %), obstructive resection — 10 (11.1 %). Acute bleeding was the manifestation of rectal cancer in 11 (10.8 %) patients. Patients underwent surgery after magnetic resonance imaging (invasion into the mesorectal fascia, prostate, vagina, sacrum; lymphadenopathy): high anterior resection — 7 (63.6 %), low anterior resection with protective ileostomy — 3 (27.3 %), extirpation of rectum — 1 (9.1 %). Removal of synchronous metastases by atypical hepatic resection was performed in 17 (21.8 %) patients. The following postoperative complications occurred in 14 (13.7 %) cases: wound suppuration, eventration, failure of anastomotic sutures, retracted colostoma, intra-abdominal bleeding, sepsis, pulmonary embolism. On-demand relaparotomy was performed in 7 patients: due to failure of anastomotic sutures, peritonitis — in 2, intra-abdominal bleeding — in 2, necrosis and colostoma retraction — in 3. Average bed day was 14.0 ± 1.1. Six (5.8 %) operated patients died. Causes of death were myocardial infarction — 1 (16.7 %), sepsis — 4 (66.7 %), pulmonary embolism — 1 (16.7 %). Conclusions. 1. Suboptimal results of providing care for patients with complicated colon cancer in Ukraine are primarily caused by the division of the problem into surgical and oncological aspects. 2. Almost every second patient with complicated colon cancer has conditions for radical surgery. 3. A comprehensive solution to the problem of complicated colon cancer is possible by organizing medical institutions in Ukraine, such as Saint Panteleimon Hospital of the First Lviv Territorial Medical Union (Lviv).